Antecedents of Healthy Food Purchase Intention Among Local Gen-Z Tourists in Bali - Richadinata, Kadek Riyan Putra; Putra, I Made Luhur Adi; Kusuma, AA Made Indra Wijaya; Pratama, Putu Yogi Agustia; Widnyani, Ni Made; Lisnawati, Ni Made Ary (Journal of Economics and Public Health, 2025)
The growing public awareness of healthy eating patterns in Indonesia has driven the consumption of organic foods and environmentally friendly products. However, despite this rising trend, not all consumers have a strong intention to purchase healthy foods. This study aims to analyze the influence of environmental concern, food quality, health consciousness, and media exposure on the intention to purchase healthy food, with subjective norm as a mediating variable. A quantitative approach was employed using Structural Equation Modeling Partial Least Square (SEM-PLS), involving 140 domestic tourists who had visited Bali, selected through purposive sampling. The research instrument was adapted from previously validated standardized scales. The analysis results show that all four independent variables significantly affect subjective norm, and subjective norm partially mediates the relationship between environmental concern, food quality, health consciousness, and media exposure with the intention to purchase healthy food. These findings highlight the importance of social influence in shaping Gen Z consumers' intention to buy healthy food. This study offers theoretical contributions to the development of the Theory of Planned Behavior (TPB) and practical insights for marketing strategies of healthy food products based on social and environmental values.